NEK2 drives pathogenesis, drug resistance, and LMP1 expression in EBV-positive non-Hodgkin lymphoma - Maria C. White; Philip T. Lange; Jessica Stewart; Blossom Damania (Proceedings of the National Academy of Sciences, 2026)
Non-Hodgkin lymphoma (NHL) is one of the most common cancers worldwide, representing 90% of malignant lymphomas. NHL is a diverse group of malignancies, and a subset of these lymphomas are caused by infection with the human gammaherpesvirus, Epstein–Barr virus (EBV). Many EBV-positive lymphomas are highly aggressive and rapidly develop resistance to treatment, leading to poor patient outcomes. Here, we identify the cellular kinase, NEK2, as a therapeutic target for EBV-positive NHL. We demonstrate NEK2 protein expression is increased in primary lymphocytes following EBV infection, and that the EBV latency proteins EBNA1, LMP1, and EBNA2 each independently drive NEK2 upregulation. We show NEK2 is necessary for the growth and survival of EBV-positive NHL, and that NEK2 inhibition selectively kills lymphoma cells but not normal lymphocytes. Inhibition of NEK2 resulted in EBV-specific inflammatory cell death characterized by reactive oxygen species accumulation and gasdermin D cleavage. Additionally, expression of the EBV oncoprotein, LMP1, and the cellular oncoprotein, c-myc, were decreased following NEK2 inhibition. Furthermore, we demonstrate multidrug resistance-associated protein 1 (MRP1) is the most active drug resistance transporter protein in EBV-positive NHL. NEK2 inhibition reduced the expression and activity of cellular drug resistance transporter proteins, including MRP1, leading to increased lymphoma cell chemosensitivity. Finally, using a humanized mouse model of EBV-driven lymphomagenesis, we demonstrate NEK2 inhibition significantly decreased tumor burden and tumor incidence while prolonging survival. Taken together, our data suggest NEK2 inhibition as a promising therapeutic strategy for EBV-positive NHL.